Exposure to models’ negative facial expressions whilst eating a vegetable decreases women’s liking of the modelled vegetable, but not their desire to eat - Edwards, Katie L.; Thomas, Jason M.; Higgs, Suzanne; Blissett, Jacqueline (Frontiers in Psychology, 2024)
Introduction Food enjoyment can be conveyed through facial expressions. Observing others’ enjoyment of food has been found to influence adults’ desirability of liked and disliked food. Exposing adults to other eaters enjoying nutritious foods that are typically disliked (e.g., vegetables) could enhance the consumption of vegetables by young adults. However, this remains to be examined in young adult populations. This study examined the effect of models’ facial expressions towards raw broccoli on young adult women’s change in liking and change in desire to eat a modelled vegetable (raw broccoli) and a non-modelled vegetable (cucumber). Methods Young adult women (N = 205) were randomised to watch a video of unfamiliar adult models eating raw broccoli with a positive, negative, or neutral facial expression. Participants’ change in liking and change in desire to eat the modelled and non-modelled vegetable was examined. Results Observing models conveying negative facial expressions whilst eating raw broccoli resulted in a statistically significant reduction in liking ratings of broccoli, but not cucumber. There was no effect of models’ facial expressions on the change in desire to eat foods. Discussion These findings suggest that watching others express a negative facial expression whilst eating a raw vegetable reduces women’s liking of the modelled vegetable, in the absence of a significant change to their desire to consume these foods. This highlights the power of others’ negative facial expressions on food liking. Further work is needed to establish the effect of others’ facial expressions on vegetable intake.